Modification of HMA using palm oil boiler ash as a filler - Shafii, Mohd Amin; Durai, Praveen Raj; Rais, Nuryantizpura Mohamad; Latif, Amminudin Ab. (International Journal of Engineering and Technology, 2018)
Waste material disposal has become a major factor in affecting the environmental condition. Palm Oil Boiler Ash (POBA) is known as one of the palm waste. In this study, a determination has been done in order to investigate the effect of POBA on the ACW 14 mix when it is added as a filler. Two different type of samples were prepared which were control sample and POBA modified samples. Control sample was prepared by using 4% of quarry dust and 2% of Ordinary Portland Cement (OPC). The POBA used in this study was sieved through the 0.075 mm sieve to obtain the portion of POBA that can be added as a filler. Inclusion of POBA was done using dry method which is by adding it together with aggregates instead of bitumen. The percentage of POBA added into the mix varied from 25% to 100% by the weight of the filler content. The Marshall Method was used to prepare both control and modified samples. Marshall stability and flow test were conducted on these samples in order to determine the strength of the mix. The results were compared between control and modified samples to determine the effect of POBA on the ACW 14 mix. From the comparison, control sample gave better results compared to the modified samples. As a conclusion, POBA affected the mixture negatively.